Nonlinear dynamics of within-host parasite competition - Rethinavel, Natarajan [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
In this thesis we study the population biology of host-parasite systems, with a systematic view of the e?ects produced by multiple infections of di?erent parasites on a same host population. This situation is akin to multiple species competing for a shared resource. As parasites compete for a host, several outcomes at the population level can appear. If both parasites cannot jointly infect the same host, then the ?ttest parasite eliminates the other. When confection is possible, the pattern changes, and coexistence of both parasites becomes possible. Finally, if a parasite can displace the other within the host, the so-called intraguild e?ect, the outcome will strongly be dependent on the income rate of new hosts, which is determined by environmental factors. We studied this system through a mathematical model which is broad enough to encompass these situations. We proceed by steps: ?rst we framed a simple mathematical model for a single parasite/host case and as we progress to other cases, our mathematical model includes new terms and ?nally it is shaped into a complete model. Our methods are twofold. We study analytically the stability of the disease-free state, which allows us to give conditions for the ability of the parasites to invade a disease-free/non-infected population. On the other hand, we resort to numerical methods to study the long-term behavior of the system, which in all cases tends to a ?xed point. The main focus is to know which parasite prevails or if they are able to coexist, and determine the conditions that regulate this outcome . Through bifurcation diagrams we analyzed the importance of the richness of the environment, de?ned by the rate of production of new hosts. We found that the long-term states depend crucially on this rate. Our main original contribution is related to the study of the intraguild e?ect. Depending of the host income rate we can have four di?erent states, which are a disease...

Nesta tese estudamos a biologia de populações de sistemas hospedeiro-parasita, com especial atenção para os efeitos produzidos por múltiplas infecções de diferentes parasitas numa dada população de hospedeiros. Tal situação se assemelha a múlpiplas espécies competindo por um mesmo recurso. Com os parasitas competindo por hospedeiros, diversos resultados no nível populacional podem ocorrer. Se ambos parasitas não puderem infectar um hospedeiro conjuntamente, então o parasita mais apto elimina o menos apto. Quando co-infecções são possíveis, o padrão muda e a coexistência pode ser estabelecida. Finalmente, se um parasita pode deslocar o outro, o assim chamado efeito intraguilda, o resultado dependerá fortemente da taxa de geração de novos hospedeiros, a qual é determinada por fatores ambientais. Nós estudamos este sistema por meio de um modelo matemático su?cientemente abrangente para dar conta destas situações. Procedemos passo-a-passo: começamos com um modelo matemático simples para o caso de um parasita e um hospedeiro. Ao progredirmos para outros casos nosso modelo matemático passa a incluir novos termos até chegarmos num modelo completo. Há dois métodos de análise envolvidos. Estudamos analiticamente a estabilidade do estado livre de infecções, o que nos permite dar condições sobre a capacidade dos parasitas de invadir uma população não infectada/parasitada. Por outro lado, usamos métodos numéricos para estudar o comportamento para grandes tempos, que em todos os casos tende a um ponto ?xo. O foco é saber qual parasita prevelacerá ou se haverá coexistência, além de determinar as condições que regulam o resultado da interação. Através de diagramas de bifurcação analisamos a importância da riqueza de recursos do ambiente, relacionada à taxa de produção de novos hospedeiros. Encontramos que os estados assimptóticos dependem fortemente...
Keywords: Biologia - População; Relação hospedeiro-parasito; Biologia - Modelos matemáticos